PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) TERHADAP HASIL BELAJAR SISWA PADA MATERI KESETIMBANGAN ION DAN pH LARUTAN GARAM KELAS XI DI SMAN 54 JAKARTA - Safitri, Nurul Febi; Sukro, Sukro; Suhartono, Suhartono (Jurnal Riset Pendidikan Kimia (JRPK), 2017)
This study aims to determine the effect of cooperative learning model type Team Assisted Individualization (TAI) on student learning outcomes on imbalance equilibrium material and pH of saline solution. This type of research is a quasi-experimental research with a Non-equivalent Control Group Design. Sampling in this research is done by Cluster Random Sampling technique. Each class has the same number of students that is 36 students. The instrument used in this study is a matter of multiple choice posttest amounted to 30 questions. The obtained data then analyzed using descriptive statistics and inferential statistics, t-test. The average learning outcomes which obtained by students in experimental class is 81.82, while in control class is 77.84. The results showed that there were differences in students' chemical learning outcomes in the experimental class and control class (tcount = 8.65; ttabel = 1.66 so tcount> ttable). Thus, it can be concluded that cooperative learning model of Team Assisted Individualization type positively influences student's chemical learning result on ionic equilibrium material and pH of salt solution due to active student during learning. Keywords: Team Assisted Individualization Learning, Learning Outcomes, Ionic Equilibrium and pH Salt Solution.